Performance of subsurface drainage systems considering groundwater flow directions and network alignment - Walaa Abd-Elaziz; Atef Elsaiad; Gehan A. H. Sallam; Alban Kuriqi; Ashraf A. Ahmed; Ismail Abd-Elaty (Frontiers in Earth Science)
Groundwater is an important water supply for households, industry, and agriculture: one-third of the world’s drinking water is sourced from groundwater. The main objective of this study is to investigate the effects of groundwater flow directions on the design of drainage plans. The study involved field investigation to measure modeling input parameters and numerical modeling using the groundwater modeling system (GMS) code. It examined the effects of a subsurface drainage system, including net drainage recharge rate, equivalent drain depth, and drain spacing. This research was applied to the real-world case of the Mashtul Pilot Area (MPA) in Egypt. The results showed that the lateral arrangement had a high performance by orienting at 90°, 135°, and 45° angles. The groundwater levels reached 5.63, 5.33, and 5.51 m above mean sea level for the three orientations, respectively, at the baseline case. Also, the results showed that decreasing the drainage rates and increasing the equivalent drain depth have a greater effect on increasing groundwater levels, while increasing drain spacing led to an increase in the groundwater levels in the study. This approach is useful for the future arrangement of lateral subsurface drainage systems, which should be laid perpendicular to the direction of groundwater flow. In addition, the feasibility of this approach should be considered in the future design of this system. The results of the current study are useful for all stakeholders.